Sudan’s Infrastructure : A Continental Perspective - Ranganathan, Rupa; Briceno-Garmendia, Cecilia M. (2012)
Improvements in infrastructure across Sudan in recent years have contributed 1.7 percentage points to the country's per capita growth. Consistent with trends in other countries, the ICT revolution that swept Africa contributed more than any other sector to growth in Sudan. Raising the infrastructure endowment of all parts of Sudan to that of the region's best performer -- Mauritius -- could boost annual growth by about 3.5 percentage points. Sudan has heavily invested in infrastructure in recent years. Notable achievements include tripling power-generation capacity, liberalizing the ICT sector, and connecting to an undersea fiber-optic cable. Looking ahead, Sudan's most pressing infrastructure challenges lie in the water and transport sectors. In the water sector, the country needs to dramatically improve access to safe sources of water and sanitation while improving utility efficiency. In the transport sector the country needs to vastly expand rural and international connectivity and improve quality across the network. Sudan presently spends about $1.5 billion per year on infrastructure, with $580 million a year lost to inefficiencies. Even if the inefficiencies were eliminated, however, Sudan would face an infrastructure funding gap of $2.9 billion per year. This gap could be reduced by half by choosing lower-cost water, sanitation, and road-surfacing technologies, and could be bridged by continuing to capture financing from the private sector and abroad.